Assessment of Target Volume Definition for Radiosurgery of Atypical Meningiomas with Multimodality Imaging - Selcuk, Demiral; Murat, Beyzadeoglu; Ferrat, Dincoglan; Omer, Sager (Journal of Hematology and Oncology Research, 2020)
Objective Meningiomas are most common intracranial benign tumors comprising around one third of all intracranial neoplasms, and typically have benign and indolent nature with slow-growing behaviour. Benign meningiomas are slow growing tumors typically following an indolent disease course. Nevertheless, atypical or anaplastic meningiomas may follow a more aggressive disease course with invasion of critical structures and recurrences. In the current study, we evaluate the incorporation of magnetic resonance imaging (MRI) for radiosurgery treatment planning of atypical meningiomas. Materials and Methods Atypical meningioma radiosurgery target volume determination with and without incorporation of MRI has been evaluated. Ground truth target volume used as the reference has been outlined by the board-certified group of radiation oncologists after comprehensive assessment, thorough collaboration and consensus. Results Target volume definition by use of Computed Tomography (CT)-only imaging and by CT-MR fusion based imaging has been comparatively evaluated in this study for linear accelerator (LINAC)-based radiosurgical management of atypical meningioma. Ground truth target volume defined by the board-certified radiation oncologists after detailed evaluation, collaboration, colleague peer review and consensus has been found to be identical to target determination by use of CT-MR fusion based imaging. Conclusion Despite significant progress in neurosurgical techniques over the years, complete surgical resection may not be feasible in the presence of meningiomas located at eloquent brain areas in close association with important neurovascular structures. RT may have a role in multidisciplinary management of meningiomas. Incorporation of MRI into treatment planning for radiosurgery of atypical meningiomas may improve target definition despite the need for further supporting evidence.
Keywords: atypical meningioma; radiosurgery; magnetic resonance imaging (MRI)